Epistemic contextualism : a defense - Baumann, Peter, Ph. D. (Oxford University Press, 2016)
This book develops and defends a version of epistemic contextualism, that is, of the view that the truth conditions or the meaning of knowledge attributions of the form "S knows that p" can vary with the context of the attributor. The first part of the book is about arguments for contextualism and develops a particular version of it. The second part of the book discusses problems contextualism faces and to which it needs to respond as well as an extension of contextualism beyond epistemology. The third part of the book is about some major objections to contextualism and about alternative views, namely subject-sensitive invariantism, contrastivism, and relativism.